Health perceptions and treatment adherence in adults with cystic fibrosis. Issue 12 (December 1996) - Abbott, J.; Dodd, M.; Webb, A. K.
Abstract : BACKGROUND: Clinical and demographic variables are poor predictors of treatment adherence. This study therefore examined the relationships between the patients' perception of their cystic fibrosis and their reported adherence to physiotherapy, exercise, pancreatic enzyme and vitamin therapies. METHODS: Sixty adults with cystic fibrosis completed the Health Perception Scale, Health Locus of Control Scale, and the Manchester Adult Cystic Fibrosis Compliance Questionnaire. RESULTS: Reported adherence to physiotherapy, exercise, pancreatic enzyme and vitamin therapies was not influenced by patients' perceptions of their past, current and future disease severity, or their perceived susceptibility to recurrent infections. The greater their level of worry regarding their disease, the more likely they were to adhere to their physiotherapy (p < 0.002), pancreatic enzyme (p < 0.001) and vitamin (p < 0.001) regimens. No difference between the exercise adherent and non-adherent groups emerged regarding their level of worry. Compared with patients who believed that they were in control of their health, those who believed that their cystic fibrosis was controlled by others (family and health professionals) reported greater levels of adherence to their physiotherapy (p < 0.001), pancreatic enzyme (p < 0.001) and vitamin (p < 0.001) therapies. In contrast, patients who adhered to their exercise regimen believed that they were in control of their disease to a greater extent than those who did not (p < 0.003). CONCLUSIONS: Worrying about cystic fibrosis and the perception of having little personal control over the disease facilitated treatment adherence. It is clear that patients perceive exercise therapy differently from other forms of treatment.